The fallacies of fractional flow reserve. (1st March 2020) - Soares, Andrea; Brown, David L.
Highlights: Fallacies of FFR Ischemia caused by a focal obstructive epicardial coronary stenosis is on the direct pathway to death or MI. The microvasculature is irrelevant in the assessment of patients with angina. FFR-guided PCI improves outcomes through targeted lesion selection. FFR-guided PCI improves outcomes compared to optimal medical therapy.